Posouzení vybraných ukazatelů pomocí statistických metod - Švestka, Milan (Vysoké učení technické v Brně. Fakulta podnikatelská, 2017)
Bakalarska prace se zameruje na zhodnoceni situace spolecnosti XYZ, za vyuziti vybranych financnich ukazatelu a statistickych metod, ktere predstavuji regresni analyzu a casove rady za obdobi let 2011 az 2016. Prace je slozena ze tri casti, kde prvni cast je zamerena na teoreticka vychodiska a popisuje jednotlive vybrane financni ukazatele, regresni analyzu a casove rady. Dalsi cast predstavuje popsani soucasneho stavu spolecnosti a poskytuje pohled na financni situaci a nastinuje mozny budouci vyvoj. Posledni cast obsahuje navrh na zlepseni a doporuceni, kterych by se mela spolecnost drzet.

Bachelor thesis focuses on the evaluation of the situation XYZ, using selected financial indicators and statistical methods representing the regression analysis and time series for the period 2011 to 2016. The thesis consists of three parts, where the first part is focused on the theoretical basis and describes individual selected financial indicators, regression analysis and time series. The next part describes the current state of the company and provides an overwiev of the financial situation of the company and outlines possible future developments. The last part constains suggestions of improvements and recommendations that the company should keep.
Assessing Selected Indicators Using Statistical Methods
Keywords: Financni analyza; statistika; regresni analyza; casove rady; ukazatele; rozvaha; vykaz zisku a ztrat.; Financial analysis; statistics; regression analysis; time series; indicators; balance sheet; profit and lost account.